The optimisation of paediatric CT examinations in Scotland: phase one; benchmarking current performance. (18th November 2021) - Worrall, Mark; MacDonald, Nicola; Gillen, Rebecca; Hince, Andrew; Hampson, Lee; Duguid, Rebecca; McCallum, Stephen; Gentle, David
Abstract: To benchmark the dose from paediatric head and chest examinations on computed tomography (CT) scanners throughout Scotland, to identify scanners that may require optimisation and to provide optimisation advice based on the protocols from better performing scanners. Anthropomorphic phantoms corresponding to 1, 5 and 10 year olds were sent to 50 CT scanners around Scotland. Head and chest examinations were undertaken by local staff using local techniques on each scanner with each phantom, and details of the protocols used were recorded. Computed tomography dose index (CTDI)vol and dose length product (DLP) were recorded post-scan. There is a significant variation in performance throughout Scotland. For head examinations, the highest DLP is 13 times the lowest for an equivalent sized phantom. For chest examinations, the highest is 128 times the lowest for an equivalent sized phantom. The wide range of CT dose measurements indicates the potential for variation in image quality across Scotland. Feedback has been provided to all participating sites on their individual results compared to the national data set. Specific feedback was provided where relevant on potential considerations for optimisation. Scanners that may be undertaking paediatric CT head and chest examinations in a sub-optimal manner throughout Scotland have been identified along with those aspects of a scan protocol that are most likely to lead to sub-optimal performance.